2014
DOI: 10.1090/s0002-9939-2014-12365-3
|View full text |Cite
|
Sign up to set email alerts
|

Positive knots and Lagrangian fillability

Abstract: This paper explores the relationship between the existence of an exact embedded Lagrangian filling for a Legendrian knot in the standard contact R 3 and the hierarchy of positive, strongly quasi-positive, and quasi-positive knots. On one hand, results of Eliashberg and especially Boileau and Orevkov show that every Legendrian knot with an exact, embedded Lagrangian filling is quasi-positive. On the other hand, we show that if a knot type is positive, then it has a Legendrian representative with an exact embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…Proof. The "if" direction is due to Hayden and Sabloff [26], who showed that all positive links bound exact Lagrangian surfaces. Conversely, suppose that K bounds a Lagrangian surface Σ.…”
Section: A Census Of Lagrangian Slice Knotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. The "if" direction is due to Hayden and Sabloff [26], who showed that all positive links bound exact Lagrangian surfaces. Conversely, suppose that K bounds a Lagrangian surface Σ.…”
Section: A Census Of Lagrangian Slice Knotsmentioning
confidence: 99%
“…In symplectic and contact topology, there has been a great deal of recent interest in the subject of Lagrangian cobordisms between Legendrian submanifolds; see for example [1,3,5,6,8,9,14,13,25,26,42]. A key motivation is that one can construct a category whose objects are Legendrian submanifolds and whose morphisms are exact Lagrangian cobordisms, and this category fits nicely into Symplectic Field Theory [15].…”
Section: Introductionmentioning
confidence: 99%
“…[29],[31]). Each positive knot, 2-bridge knot, and +-adequate knot has a Legendrian representative that does not have an exact, nonorientable Langrangian endocobordism.…”
mentioning
confidence: 99%
“…In this section, we illustrate the possibilities of the construction in two families of examples. As noted in the introduction, deeper applications of these constructions appear in [6,8,28,38].…”
Section: Constructions In Dimensionmentioning
confidence: 97%